Edukasi Gizi Seimbang Terhadap Pengetahuan dan Sikap Remaja Pada Masa Covid-19 - Ernawaty Siagian (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2023)
Background: Adolescence is a condition where there is a transition from childhood to adulthood. These changes result in physical changes and psychological changes spesifically. Increasing the knowledge and attitudes of adolescents about balanced nutritional needs so that they are able to live a healthy life with appropriate food consumption patterns that meet the criteria for balanced nutrition and minimize the occurrence of nutritional issues in adolescents. Objectives: The purpose of this study is to find whether there is a significant difference between balanced nutrition education on knowledge and attitudes of adolescents before and after intervention in adolescents. Methods: This study used a pre-experimental design method. The form of experimental design used by OneGroup is pretest – post test design. Sampling using total sampling technique sample. The researcher first gave question as pre-test data and then given intervention in the form of education using video media, counselling and intervention leaflets for 3 meetings then carried out the post-test again. The population is the 8th grade students of SMP Advent Bandar Lampung. The statistical test used is the parametric test (Dependent paired T-test). Results: The result of the analysis showed that there was a significant relationship between the level of knowledge and attitudes before and after the intervention was given with a sig value of 0.000 (p<0.05). Conclusion: There is a relationship between the effect of balanced nutrition education on knowledge and attitudes. Through video media, counselling, and leaflets can be recommended as effective communication media because they can contain a lot of information about educational materials.